(untitled) (Research, Society and Development, 2020)
This longitudinal observational study was developed to describe thermal stress indexes, the physiological response, and the energy status in Girolando cows raised on pasture in the tropical savannah during the transition and voluntary waiting periods. Twenty Girolando cows were evaluated. The temperature and humidity index (UTI) and the globe temperature and humidity index (ITGU) were measured daily, and cows were assessed and submitted to blood collection at time intervals distributed among the three weeks before calving until the 60th day postpartum. Rectal Temperature, Heart Rate, and Respiratory Rate (TR, FC, and FR) were measured in the morning (6:00 - 8:00 hours) and the afternoon (14:00 - 16:00 hours). TR and FR were used to calculate the Benezra Comfort Index (ICB) and FR to calculate the Iberian Heat Tolerance Index (ITCI). The energy status was evaluated by the levels of glucose, non-esterified fatty acids (AGNEs), beta-hydroxybutyrate (βHB), triglycerides, cholesterol, and HDL. In the period of 8:00 to 16:00 hours, the mean values of ITU ranged from 73.5 to 78.7 and of ITGU from 81.8 to 88.2, characterizing exposure to thermal stress condition. The variables FC, FR, and TR, differed between morning and afternoon (p<0,05), as well as the ICB and ITCI (P<0,01). Mean glucose levels were similar in prepartum, with a drop on the day of calving, reaching the lowest level on the 5th day postpartum. For AGNEs, the highest value was found on the day of calving, with a subsequent decrease (p<0,05); βHB decreased until the week before calving and increased both on the day of calving and after (p>0.05). From the day of calving, triglyceride levels decreased (p<0,05), but cholesterol and HDL increased (p<0,05). As for the reproductive variables, the first service was influenced by the ITU and ITGU at the time of the first service, as well as by the ICB and ITCI. The environmental indexes indicated that Girolando cows suffered thermal stress during the afternoon period, but this did not influence the energy status during the transition and voluntary waiting periods, which remained within the expected metabolic status in this productive phase of the dairy cow. Correlations between comfort index (ICB) and heat tolerance (ITCI) with respiratory rate and rectal temperature indicate that they should be used to assess the thermal comfort of Girolando cows raised on pasture in the tropical savannah.